Analisis Tabungan Pendidikan Syari’ah sebagai Instrument Perencanaan Keuangan Keluarga - Ilmiyah, Izzatul; Istingadah, Istingadah (Program Studi Perbankan Syariah STAI Senori Tuban, 2025)
The rising cost of education poses a significant challenge for families in maintaining financial stability, particularly amid fluctuating economic conditions. For Muslim families, financial planning must not only consider economic aspects but also comply with Islamic principles. Sharia-based education savings emerge as a solution to support long-term financial planning for children’s education in alignment with Islamic values. This study aims to analyze the effectiveness and contribution of Sharia education savings as a financial planning instrument for Muslim families, as well as to evaluate the application of Sharia principles in such products. A qualitative approach was employed using library research methods, with data collected from various sources, including books, scholarly journals, DSN-MUI fatwas, and official documents from Islamic financial institutions. The data were analyzed using content analysis with a descriptive analytical approach. The findings reveal that Sharia education savings can serve as an effective financial instrument for Muslim families in preparing education funds in a systematic and Sharia-compliant manner. The product emphasizes transparency in contracts and avoids elements of riba (interest), gharar (uncertainty), and maysir (speculation). However, challenges remain, particularly in the form of low Sharia financial literacy and limited public understanding of the product’s benefits.